Family-Friendly Policies on Job Stress mediated by Work-Family Conflict (Bank Jambi Central Office) - Ikhwani, Fesha Syeiva; Probosari, Ninik (Universitas Mercu Buana, 2024)
This study aims to identify and analyze the effect of Family-Friendly Policies on Job Stress with Work-Family Conflict as a Mediating Variable (Study at Bank Jambi Central Office). This type of research is quantitative research. The method used is the Structural Equation Model (SEM) method with the help of SmartPLS 4. The population of this study is all female permanent employees at Bank Jambi Central Office as many as 52 peoples. The sampling technique used is Non Probability Sampling with saturated sampling (census) so that the entire population is used as a sample of 52 peoples. The results of the study show that: 1. Family-friendly policies have a significant positive effect on work stress on female permanent employees at Bank Jambi Central Office. 2. Work-family conflict cannot mediate the role of family-friendly policies on stress on female permanent employees at Bank Jambi Central Office. Thus supervisors can fulfill family-leave polices in the form of granting permits or urgent leave (1-2 days) to fulfill their responsibilities as a mother to care for their child who is sick or also the company can provide facilities in the form of assistance with medical expenses. In addition, the Bank Jambi Central Office can facilitate employees in the form of providing Child Daycare (TPA) around the office to make it easier for employees to supervise children at a closer distance while completing office work.So that these female employees can balance life as family members, namely as a mother who gives attention and affection to her child and as an office employee who must complete her job responsibilities.